Air non-thermal plasma, a green approach for the treatment of contaminated water: the case of sulfamethoxazole - Giardina, Agata; Lofrano, Giusy; Libralato, Giovanni; Siciliano, Antonietta; Marotta, Ester; Paradisi, Cristina (Frontiers in Environmental Chemistry, 2024)
Non-thermal plasma (NTP) is gaining increasing attention as a promising approach for advanced water treatment to degrade persistent organic pollutants. Aqueous solutions of sulfamethoxazole (4-amino-N-(5-methylisoxazol-3-yl)-benzensulfonamide, SMZ), an antibiotic largely employed for humans and animals and a widespread persistent pollutant of waters and wastewaters, were subjected to air NTP treatment in a dielectric barrier discharge reactor (DBD). The effects of SMZ initial concentration and of the solution pH on its decomposition kinetics and transformation products were investigated. Efficient degradation was achieved, resulting in the complete removal of SMZ (10 M initial concentration) in less than 25 min treatments, in the exhaustive mineralization (a result never reported before in plasma treatments and seldom reached also with other advanced oxidation processes) of all organic carbon in 6 hr and in an energy efficiency of 6.4 g/kWh at 50% conversion. By means of HPLC-UV/Vis and LC-ESI-MS n analyses, a number of organic transformation products was identified along the path to SMZ mineralization, all present always in very small amounts and in turn decomposed at short treatment times. The effect of the solution pH on the genesis and decay of transformation products was also investigated. Based on comparisons with literature data and on previous findings obtained with the DBD reactor used in this work, it is concluded that the major reactive species involved in the degradation of SMZ are the hydroxyl radical and ozone. Finally, toxicological analyses of water initially containing 0.5 mM SMZ and subjected to 4 h NTP treatment showed that the byproducts are not toxic to Raphidocelis subcapitata and Daphnia magna, while residual toxicity was detected by Aliivibrio fischeri.